Relationship between Treatment Age and Poor Outcome in Slipped Capital Femoral Epiphysis - Yusuf Alper Katı; İsmail Dikmen (Acta Medica Alanya)
Aim; Slipped capital femoral epiphysis(SCFE) is an adolescent disease characterized by the slippage of the femoral head epiphysis from the femoral neck. The aim of this study is evaluate the factors affecting clinical outcome the surgical treatment of patients diagnosed with SCFE.Methods; Patients who were admitted to the orthopedic outpatient clinic with the complaint of gait disturbance and underwent surgery with a diagnosis of SCFE and were followed for minimum one year were screened between January 2015 and December 2019. A total of 11 patients, 7 boys and 4 girls, included in the study, were followed mean 27 months (12-47). The degree of deviation was measured with Southwick's method. Both preoperative and postoperative hip clinical evaluation was performed using Heyman and Herndon Classification.Results; The mean age of the patients was 12.45 (10-14). In the perioperative period, the mean BMI of the patients was measured as 26.15 (20.45-32.34) kg/cm2. Lateral radiographs of the affected hips were taken and measured using the Southwick method, and the mean angle was 45,490 (24,30-65,70). Heyman and Herndon classification was evaluated in two main groups clinically. There was no statistically significant difference between the first group and the second group in terms of gender, side, BMI, Southwick value, time between the first symptom and presentation, and the time between presentation and diagnosis. However, the mean age of the first group, whose postoperative Heyman and Herndon classification was evaluated as excellent and good, was statistically lower than the second group (p = 0.016). In addition, while no negative change was observed in the clinical score in any of the treated patients, improvement was observed in 6 patients and it was found that the preoperative score was significantly increased compared to the postoperative evaluation (p = 0.014).Conclusion; In situ fixation with a single cannulated screw and early surgical treatment are two important factors in achieving good clinical results in patients with SCFE. It should be kept in mind that patients diagnosed with SCFE at an older age may also be associated with poor clinical results.